2022
DOI: 10.7717/peerj.13252
|View full text |Cite
|
Sign up to set email alerts
|

Fungal communities represent the majority of root-specific transcripts in the transcriptomes of Agave plants grown in semiarid regions

Abstract: Agave plants present drought resistance mechanisms, commercial applications, and potential for bioenergy production. Currently, Agave species are used to produce alcoholic beverages and sisal fibers in semi-arid regions, mainly in Mexico and Brazil. Because of their high productivities, low lignin content, and high shoot-to-root ratio, agaves show potential as biomass feedstock to bioenergy production in marginal areas. Plants host many microorganisms and understanding their metabolism can inform biotechnologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Also, cultivar interactions with sisal microbiome might be unique. Even though taxonomically similar microorganisms in A. sisalana and H11648 were found, transcriptomic analysis of these fungi revealed that the same groups might be using different metabolisms in each cultivar (Marone et al, 2022). The combination of these specific mechanisms may contribute to robust hybrids that simply make them healthier and, therefore, more able to deal with pathogenic microorganisms, such as A. welwitschiae.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cultivar interactions with sisal microbiome might be unique. Even though taxonomically similar microorganisms in A. sisalana and H11648 were found, transcriptomic analysis of these fungi revealed that the same groups might be using different metabolisms in each cultivar (Marone et al, 2022). The combination of these specific mechanisms may contribute to robust hybrids that simply make them healthier and, therefore, more able to deal with pathogenic microorganisms, such as A. welwitschiae.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an enriched metabolic pathway of Plantpathogen interaction (ko04626; p.adjust = 0.00014) was identified, suggesting the presence of a phytopathogen. Recent studies using this same transcriptomic dataset have described several viral (Quintanilha-Peixoto et al, 2021) and fungal (Marone et al, 2022) interactions in A. sisalana, so this metabolic pathway might be a response to these interactions. Furthermore, the flavonoid biosynthesis pathway (ko00941; p.adjust = 0.03169) enrichment and the accumulation of these bioactive compounds in Agave species (Barriada-Bernal et al, 2014;Ahumada-Santos et al, 2013;Morreeuw et al, 2021) may indicate protection against these phytopathogens (Ferreyra.…”
Section: Go and Kegg Enrichment Analysismentioning
confidence: 97%
“…In addition, an enriched metabolic pathway of Plant-pathogen interaction (ko04626; p.adjust=0.00014) was identi ed, suggesting the presence of a phytopathogen. Recent studies using this same transcriptomic dataset have described several viral (Quintanilha-Peixoto et al, 2021) and fungal (Marone et al, 2022) interactions in A. sisalana, so this metabolic pathway might be a response to these interactions. Also, Flavonoid biosynthesis (ko00941; p.adjust=0.03169) enriched may indicate the protection of A. sisalana against these phytopathogens (Falcone Ferreyra et al, 2012).…”
Section: Go and Kegg Enrichment Analysismentioning
confidence: 98%
“…The GO enrichment of darkolivegreen module shows processes related to regulation of defense response to fungus, brassinosteroid biosynthetic process, and positive regulation of transcription initiation from RNA polymerase II promoter. Indeed, fungal transcripts were described in the same dataset (Marone et al, 2022). Although most fungal transcripts were root-speci c, some were present in the stem.…”
Section: Co-expression Network Analysismentioning
confidence: 99%